THE PRODUCTIVITY OF FOUR FODDER BEET CULTIVARS (BETA VULGARIS VAR. CRASSA) AFFECTED BY AUTUMN AND WINTER SOWING - Al-Jbawi, Entessar; Bagdadi, Mohamad; Nemr, Yousef (International Journal of Environment, 2015)
There is renewed interest in fodder beet (Beta vulgaris L.) production in Syria. However, recommended agronomic practices for maximizing productivity are limited. A field experiment was conducted in season 2011-2012 to study the effect of autumn and winter sowing on yields and its components of four fodder beet cultivars. The experiment was a randomized complete block design (RCBD) in split plots arrangement with three replicates, sowing dates were assigned to the main plots and fodder beet cultivars (Jamon, Splendids, Starmon and Vermon) were allotted to the sub plots. The results of T-Test exhibited the superiority of autumn date as compared with winter date, but in a small percentage. Sowing dates and varieties exhibited highly significant (p?0.05) differences in most of the studied characteristics (shoot weight.plant-1, root/shoot ratio, root and shoot yield (t.ha-1). Varieties affected all of the production traits significantly (p?0.05). Vermon surpassed the other cultivars in terms of the production studied traits. The conclusion is to sow fodder beet in autumn time in Al Raqqa, Syria, to attain the highest yield and yield components traits. Also The study recommends further trials identify optimum agronomic practices especially harvesting date, soil type, land preparation, fertilization and spacing in the other sites in Syria. International Journal of Environment Volume-4, Issue-3, June-August 2015 Page: 121-129